Time-Resolved Spectroscopy Diagnostic of Laser-Induced Optical Breakdown. (15th September 2009) - Parigger, Christian G.; Hornkohl, James O.; Nemes, László
Abstract : Transient laser plasma is generated in laser-induced optical breakdown (LIOB). Here we report experiments conducted with 10.6-micronCO 2 laser radiation, and with 1.064-micron fundamental, 0.532-micron frequency-doubled, 0.355-micron frequency-tripled Nd:YAG laser radiation. Characterization of laser induced plasma utilizes laser-induced breakdown spectroscopy (LIBS) techniques. Atomic hydrogen Balmer series emissions show electron number density of10 17 cm − 3 measured approximately 10 μ s and 1 μ s after optical breakdown forCO 2 and Nd:YAG laser radiation, respectively. Recorded molecular recombination emission spectra of CN andC 2 Swan bands indicate an equilibrium temperature in excess of 7000 Kelvin, inferred for these diatomic molecules. Reported are also graphite ablation experiments where we use unfocused laser radiation that is favorable for observation of neutralC 3 emission due to reducedC 3 cation formation. Our analysis is based on computation of diatomic molecular spectra that includes accurate determination of rotational line strengths, or Hönl-London factors.